PENGARUH KUALITAS KEHIDUPAN KERJA DAN KEPUASAN KERJA TERHADAP KETERLEKATAN PEGAWAI GENERASI Y DI KABUPATEN BIMA - Hawariah Hawariah; Jaenab Jaenab; Khairul Amar (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The purpose of this study is to determine the significant partial influence of Quality of Work-life on Employee Engagement, the significant partial influence of Job Satisfaction on Employee Engagement, the significant simultaneous influence of Quality of Work-life and Job Satisfaction on Employee Engagement of Generation Y in Bima Regency. The instrument in the study used a questionnaire with a Likert scale. The population in this research are Millennial of Generation working in The Government office and The Grocery Stores in Bima Regency specially Lambu Subdistrict. They have age 39 year old (1981) and 27 year old (1996). This research use Lemeshow Formula to take some Sample because population in this research is not known exactly. The Sample in this research are amount 96 employees. Data collection techniques included observation, questionnaires, and literature studies. Data analysis techniques used validity tests, reliability tests, classical assumption tests, multiple linear regression tests, correlation coefficient tests, determination tests, t tests, and f tests with the help of SPSS version 16 for Windows. The results of this study indicate that 1) Quality of work life has a significant effect on the engagement of generation Y employees in Bima Regency. 2) Job satisfaction has a significant effect on the engagement of generation Y employees in Bima Regency. 3) Quality of work life and job satisfaction have a significant effect simultaneously on the engagement of generation Y employees in Bima Regency.